MENGAPA LEMBAGA ZAKAT DIPILIH?: PENDEKATAN MULTICRITERIA DECISION MAKING - Aam Rusydiana (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
Islamic finance is also known as a social financial entity that also has an equally important role for public benefit. One of Islamic social financial instrument is zakat. Typically, zakat are managed by an institution known as amilin or the management of zakat. This study tries to analyze the preferences and behavior of criteria for selection of zakat institution or amil zakat in Indonesia through the multicriteria decision making method known as Analytical Hierarchy Process (AHP) approach.The results conclude that the most priority criteria that influence the selection of zakat institution in Indonesia are innovative program, professional and financial transparency/accountability. Therefore, zakat managers or amilin must always be innovative and professional for managing zakat and social funds. In addition, trustworthy and fully responsible managers are needed in managing zakat funds.